Halal Tourism as a Means of Empowering the People's Economy - Fathan Budiman Fathan; M. Mustahal; Abdul Basit (Indonesian Academy of Social and Religious Research (IASRR), 2022)
This study aims to explain the economic empowerment of the people based on halal tourism based on the Qur'an. The large number of global Muslim tourists visiting Indonesia, makes halal tourism potential to be one of the sectors driving Indonesia's halal industry. There are no less than 140 million Muslim tourists with online shopping of USD 35 billion every year. This is a challenge as well as an opportunity to make halal tourism a national tourism industry and a means of empowering the people's economy. This study used descriptive qualitative method. The results of the study indicate that the development of halal tourism can be used as a means to empower the people's economy. Opening up greater job opportunities thereby reducing unemployment. Improving the welfare of the people by opening up business and job opportunities. Can increase the income of the people so that it has an impact on increasing the ability of the community to be able to live more prosperously.